2011
DOI: 10.5194/angeo-29-157-2011
|View full text |Cite
|
Sign up to set email alerts
|

Mid-latitude Summer Nighttime Anomaly (MSNA) – observations and model simulations

Abstract: Abstract. In this paper, we present model simulations of the Mid-latitude Summer Nighttime Anomaly (MSNA) in the Northern Hemisphere, which is characterized by noontime dip and evening maximum in the diurnal variation of the ionospheric density. The simulations are carried out using SUPIM (Sheffield University Plasmasphere Ionosphere Model) for solar minimum at 135 • E longitude where MSNA is most pronounced in the Northern Hemisphere. The simulations are used to understand the relative importance of electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 36 publications
3
51
0
2
Order By: Relevance
“…Liu et al (2010) indicate that the two or three distinct regions of the MSNA results from a combination of the neutral wind effect in the geomagnetic frame, photoionization, and the thermal contraction of the ionosphere at sunset. The simulations of Thampi et al (2011) and Chen et al (2011) reach similar conclusions that the neutral wind is the dominant effect, and the zonal electric field can also contribute to modify the MSNA. Meanwhile, scientists Zakharenkova et al 2012;Cherniak et al 2014) examine storm effects providing further evidence to the pivot role of effective neutral wind in the formation of MSNA.…”
Section: Introductionsupporting
confidence: 59%
“…Liu et al (2010) indicate that the two or three distinct regions of the MSNA results from a combination of the neutral wind effect in the geomagnetic frame, photoionization, and the thermal contraction of the ionosphere at sunset. The simulations of Thampi et al (2011) and Chen et al (2011) reach similar conclusions that the neutral wind is the dominant effect, and the zonal electric field can also contribute to modify the MSNA. Meanwhile, scientists Zakharenkova et al 2012;Cherniak et al 2014) examine storm effects providing further evidence to the pivot role of effective neutral wind in the formation of MSNA.…”
Section: Introductionsupporting
confidence: 59%
“…We then compared the results obtained by us in 2008 to the measurements conducted in Japan in July 2008 at the center of the northeastern Asia anomaly zone (Thampi et al, 2011). These measurements were con ducted by radio occultation, which makes it possible to obtain the electron concentration profile beginning from the bottom layer and up to heights substantially exceeding the height of the layer maximum.…”
Section: Measurement Methods and Resultsmentioning
confidence: 97%
“…These measurements were con ducted by radio occultation, which makes it possible to obtain the electron concentration profile beginning from the bottom layer and up to heights substantially exceeding the height of the layer maximum. Thampi et al (2011) showed that the local time corresponding to the night maximum peak depends on geographic latitude: the time shifts towards midnight at the increase in latitude. For the geographic latitude of 45°N…”
Section: Measurement Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thampi et al (2011) showed that the formation of the mid-latitude summer nighttime anomaly (MSNA) is closely related to diurnal variation in the neutral winds, but with little contribution from the changes in the electric fields. The observed features of the MSNA are reproduced better when MU radar winds are used as the model input rather than HWM93 winds.…”
Section: Remarks and Conclusionmentioning
confidence: 99%